Territorial institutions of Olonets province and Stolypin agrarian reform - Badanov Vadim Georgiyevich (Studia Humanitatis, 2022)
The article examines the activities of territorial institutions (zemstvo) of the Olonets province during the period of P.A. Stolypin agrarian reform. The attitude of zemstvo activists to the peasant community and to the agro-technical innovations of the government is analysed. The assistance of zemstvo agronomy in carrying out reform, in maintaining and developing peasant farms in the Olonets province is being considered. The article also analyses the appeal of Olonets territorial institutions to the Finnish agrarian experience.